Engineering Properties of Clayey Soil Stabilized with Lime - Alrubaye, Ali Jamal; Muzamir, Hasan; Fattah, Mohammed Y. (Asian Research Publishing Network (ARPN), 2016)
Kaolin soil represents the soft clay soil with a depleted bearing capacity and an elevated compressibility level. Thus, in order to hold up civil structures, the bearing capacity of kaolin soil needs to be raised. Several soil improvement procedures are currently available. These include soil replacement, preloading, corduroy and chemical stabilization. However, as these procedures are harmful to the environment, efforts to achieve soil stabilization ought to make use of materials that are environmentally friendly. The utilization of industrial waste that does not have a negative impact on the environment would represent a significant step forward in this area. Among the most frequently employed procedures to achieve soil stabilization is the utilization of a binder such as lime. This study puts forward an array of laboratory investigations to assess the influence of lime on the compressibility and swelling traits of soil. According to the findings, the liquid limit and plasticity index of soil is reduced with the introduction of lime. Pozzolanic reactions transpire due to the siliceous and aluminous nature of the material which has a negligible cementation value and is made up of large particles. This circumstance culminates in a reduction of the liquid limit. With a 9% application of lime, an elevation in the liquid limit was observed (a decrease in other reaction materials). This is attributed to the excessive presence of lime. The optimal water content rose from 20% to 23% with a 5% application of lime. The stabilizer content (lime) reduces the maximum dry density from 1.63 to 1.585 g/cm3. Lime content enhances the compressibility of soft clay by lowering the coefficient of volume compressibility (mv) reduces with increasing stabilizer content and the optimum percent for lime. This is a result of the reaction between lime and soil.